Usaha Guru Dalam Mewujudkan Keaktifan Belajar Siswa dengan Media Daring Mata Pelajaran Akidah Akhlak di MI Ulumiyah Pare Kediri - Yasin Nurfalah; Muslimin (eL Bidayah: Journal of Islamic Elementary Education, 2022)
The COVID-19 pandemic has brought major changes to the teaching and learning process, including activating Madrasah Ibtidaiyah (MI) students in Akidah Akhlak subjects through bold media. So the researcher aims to analyze the efforts made by the teacher in realizing student learning activities in the Akidah Akhlak subject through the PAKEM method at MI Ulumiyah Tertek Pare Kediri, the application of the PAKEM method in learning Akidah Akhlak to realize student learning activities at MI Ulumiyah Semanding Tertek Pare Kediri, and The background that supports and hinders the efforts made by the teacher in realizing student learning activities in the Akidah Akhlak subject through the PAKEM method at MI Ulumiyah Semanding Tertek Pare Kediri. This type of research is qualitative, the data collection method uses observation, interviews/interviews, and documentation. The results of the study show that the teacher's efforts in realizing student learning activity in the moral aqidah subjects by applying PAKEM learning, namely, the intrinsic effort that is different and depends on each individual, while the extrinsic effort is to activate students in learning and create long-term memories in students. The application of PAKEM in learning includes differences in tools and media used because the learning process is carried out through courage, so students practice at home according to the general equipment in their respective homes. The background is a strong commitment, the creative attitude of the teacher, and a reliable managerial head of the madrasa [Pandemi COVID-19 membawa perubahan besar dalam proses belajar mengajar, termasuk mengaktifkan siswa Madrasah Ibtidaiyah (MI) pada mata pelajaran Akidah Akhlak melalui media bold. Maka peneliti bertujuan untuk menganalisis upaya yang dilakukan guru dalam mewujudkan aktivitas belajar siswa pada mata pelajaran Akidah Akhlak melalui metode PAKEM di MI Ulumiyah Tertek Pare Kediri, penerapan metode PAKEM dalam pembelajaran Akidah Akhlak untuk mewujudkan aktivitas belajar siswa di MI Ulumiyah Semanding Tertek Pare Kediri, dan Latar belakang yang mendukung dan menghambat upaya yang dilakukan guru dalam mewujudkan kegiatan belajar siswa pada mata pelajaran Akidah Akhlak melalui metode PAKEM di MI Ulumiyah Semanding Tertek Pare Kediri. Jenis penelitian ini adalah kualitatif, metode pengumpulan datanya menggunakan observasi, wawancara/ wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa upaya guru dalam mewujudkan aktivitas belajar siswa pada mata pelajaran aqidah akhlak dengan menerapkan pembelajaran PAKEM yaitu, upaya intrinsik yang berbeda-beda dan tergantung pada masing-masing individu, sedangkan upaya ekstrinsik adalah mengaktifkan siswa dalam belajar dan menciptakan ingatan jangka panjang pada siswa. Penerapan PAKEM dalam pembelajaran meliputi perbedaan alat dan media yang digunakan karena proses pembelajaran dilakukan melalui keberanian, sehingga siswa berlatih di rumah sesuai dengan perlengkapan umum di rumahnya masing-masing. Dilatarbelakangi komitmen yang kuat, sikap kreatif guru, dan pimpinan madrasah yang handal]